Dopaminergic Modulation of Cognitive Control: Distinct Roles for the Prefrontal Cortex and the Basal Ganglia - van Schouwenburg, Martine; Aarts, Esther; Cools, Roshan (Current Pharmaceutical Design, 2010)
Evidence from psychopharmacological functional neuroimaging begins to elucidate the neurochemical mechanisms of cognitive control. Here the role of dopamine in two subcomponent processes of cognitive control is discussed: the active maintenance and the flexible updating of goal-relevant representations. A range of studies have highlighted a role for the prefrontal cortex (pFC) and its modulation by dopamine in the active maintenance of distractor-resistant goal-relevant representations. This work suggests that dopamine might modulate top-down signals from the pFC, thereby increasing the activity of posterior cortical regions that process goalrelevant representations and rendering them distractor-resistant. Conversely, other studies highlight a role for dopamine in the basal ganglia in cognitive switching, which might reflect a modulation of the selective gating of cortical cognitive and motor programs. We present a working hypothesis that integrates these two disparate literatures and states that the flexible adaptation of current goal-relevant representations is mediated by modulatory influences of activity in the dopamine-sensitive basal ganglia on connectivity between the prefrontal cortex and posterior cortex.
Keywords: Parkinson' s disease